Review and Analysis of Philippine Federalism - Andres Hinayas; Vicente Betarmos Jr; Leomarich Casinillo; Melbert Hungo (Universidade Estadual de Alagoas, 2024)
This study was conducted to provide a comprehensive review of the structure, quality, operations, and readiness of a federalist government from the perspectives of various columnists and editorials. The study employed a descriptive design aimed at discussing a specific topic or issue under investigation. Qualitative content analysis was utilized to examine the diverse opinions of columnists and editorials on Federalism, gathered from thirty (30) news articles from three nationally circulated newspapers and research papers. The online-retrieved data were printed, read, and analyzed to grasp the depth of the concepts. The study highlighted that writers in national newspapers focus on key federalism themes like decentralization, service efficiency, operational clarity, and provincial readiness. These discussions aim to inform the national and international audience about the adoption of federalism as the Philippines' new governance system. Hence, it is concluded that writers in a nationally circulated newspaper in the Philippines discuss key aspects of federalism, including decentralization for increased autonomy, focus on service quality and efficiency, clear allocation of functions for governance efficiency, and provinces' readiness to embrace federalism, facilitating a smooth transition to this new form of government. Additionally, recommendations such as adopting federalism successfully in the Philippines, key strategies involving education campaigns, stakeholder engagement, and local capacity building to empower institutions for a well-informed transition are considered.